2018
DOI: 10.1007/s13300-018-0409-1
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of Patients with Type 2 Diabetes in China: Associations of Hypoglycemia with Health Care Resource Utilization and Associated Costs

Abstract: IntroductionThis study aimed to examine the associations of hypoglycemia with health care resource utilization (HCRU) and health care costs among patients with type 2 diabetes mellitus (T2DM) in China.MethodsThis retrospective cohort study was conducted with 23,680 T2DM patients >18 years old who visited the Second Affiliated Hospital of Nanchang University between 1 January 2011 and 31 December 2015. Univariate descriptive statistics were used to relate the HCRU and associated costs to patient characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A J-shaped relationship was found between the glycated hemoglobin and all-cause mortality with an increasing death at both high and low HbA1c [4], a recent study showed an inverse or U-shaped relationship between the HbA1c and death among patients with diabetes and heart failure especially among patients who were on insulin, sulphonylureas and thiazolidinediones [5]. Hypoglycemia among patients with diabetes is associated with an increasing health-related expenditure and healthcare resources utilization [6]. In the United state a single episode of hypoglycemia requiring a healthcare provider assistance is estimated at $1161 and 160 for direct and indirect costs respectively, a study conducted in Korea found that, the cost of a single hypoglycemic attack ranged from $17.28 to $1857.09 for secondary and tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…A J-shaped relationship was found between the glycated hemoglobin and all-cause mortality with an increasing death at both high and low HbA1c [4], a recent study showed an inverse or U-shaped relationship between the HbA1c and death among patients with diabetes and heart failure especially among patients who were on insulin, sulphonylureas and thiazolidinediones [5]. Hypoglycemia among patients with diabetes is associated with an increasing health-related expenditure and healthcare resources utilization [6]. In the United state a single episode of hypoglycemia requiring a healthcare provider assistance is estimated at $1161 and 160 for direct and indirect costs respectively, a study conducted in Korea found that, the cost of a single hypoglycemic attack ranged from $17.28 to $1857.09 for secondary and tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][19][20][21]23,24 Follow-up data from the ACCORD, ADVANCE and VADT trials suggest elderly patients with a longer duration of diabetes are unlikely to gain macrovascular benefits from intensive glycaemic control and may be exposed to excess risk of severe hypoglycaemia, increased morbidity and mortality. 6,11,12,18 These findings are expanded upon in a study by Monami et al: follow-up over 6 years in those with a longer diabetes duration (10 years and over) showed that mortality only increases when HbA 1c levels are greater than 68 mmol/mol (>8.4%). 25 Similarly, over the same follow-up when considering those aged 71 years and over, mortality was shown to increase only when HbA 1c levels rose above 68 mmol/mol (>8.4%).…”
Section: Individualising Glycaemic Targets In Response To Patient Fac...mentioning
confidence: 87%
“…Concurrence of themes between articles resulted in the determination of key patient factors where individualised HbA 1c targets were beneficial. These factors were: > presence of established cardiovascular disease [5][6][7][8][9][10][11][12][13][14] > advancing age and diabetes duration 6,11,12,[14][15][16][17][18][19][20][21][22][23][24][25] > presence of frailty, disability, cognitive impairment or comorbidity 6,11,12,14,[26][27][28][29][30][31][32][33][34][35][36] > presence of problematic hypoglycaemia 18,20,[37][38][39][40][41][42][43]…”
Section: Individualising Glycaemic Targets In Response To Patient Fac...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the report, patients with T2DM spent more than 7 days in hospital on average, and each hospitalization cost was more than 6000 yuan, accounting for more than 20% of China’s urban per capita disposable income (31 195 yuan) in 2015. 21 Studies also showed that the largest share of expenditures among the T2DM-related direct medical costs was for hospitalizations (50%-55%). T2DM-related complications often contribute to hospitalizations.…”
Section: Discussionmentioning
confidence: 99%